2021
DOI: 10.1002/lt.26250
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Outcomes of Pediatric Living Versus Deceased Donor Liver Transplantation Recipients: A Systematic Review and Meta‐analysis

Abstract: Living donor liver transplantation (LDLT) emerged in the 1980s as a viable alternative to scarce cadaveric organs for pediatric patients. However, pediatric waitlist mortality remains high. Long‐term outcomes of living and deceased donor liver transplantation (DDLT) are inconsistently described in the literature. Our aim was to systematically review the safety and efficacy of LDLT after 1 year of transplantation among pediatric patients with all causes of liver failure. We searched the MEDLINE, Medline‐in‐Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 43 publications
(116 reference statements)
2
29
0
Order By: Relevance
“…19 Multiple studies have already demonstrated the survival benefit of LDLTs toward achieving superior posttransplant survival in comparison with deceased donor transplants in children. [4][5][6][7]11,12 This study is novel in demonstrating the pretransplant waiting list survival benefit of LDLTs. Given that we found that LDLT center volume is associated with lower overall waiting list dropout at the center, the availability of LDLT at a center may actually benefit all candidates listed at that center by also decreasing the competition for size-matched deceased donor grafts, although additional studies focused on this potential indirect impact of pediatric LDLTs are needed to definitively make this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…19 Multiple studies have already demonstrated the survival benefit of LDLTs toward achieving superior posttransplant survival in comparison with deceased donor transplants in children. [4][5][6][7]11,12 This study is novel in demonstrating the pretransplant waiting list survival benefit of LDLTs. Given that we found that LDLT center volume is associated with lower overall waiting list dropout at the center, the availability of LDLT at a center may actually benefit all candidates listed at that center by also decreasing the competition for size-matched deceased donor grafts, although additional studies focused on this potential indirect impact of pediatric LDLTs are needed to definitively make this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Superior graft and patient survival have been described in pediatric LDLT compared with deceased donor liver transplantation. [14][15][16] In 2019, 14% of pediatric liver transplantation registrants underwent LDLT, but this was not further stratified by race or ethnicity. [5] For Black children, Mogul et al found a reduced incidence of LDLT (subhazard ratio, 0.56) compared with White children using Scientific Registry of Transplant Recipients (SRTR) data.…”
Section: Referral and Listing For Transplantationmentioning
confidence: 99%
“…Reasons for this are likely multifactorial, reflecting improvements in organ allocation for pediatric recipients and Status 1b designation for many of the metabolic and malignancy patients; however, additional factors such as lack of surgical expertise and societal barriers are also likely contributors. [ 21 ] As LDLT was shown to be protective in our multivariable model and has been shown by others to provide superior outcomes, [ 22,23 ] it will be important to prioritize how additional resources could be applied to enable infrastructure development and resource allocation that support broad LDLT use. Furthermore, perioperative IS regimens do not reflect long‐term management, and adherence to IS therapy has been well recognized to impact long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%